Relationship between the Changes of VEGF Level and Dendritic Cells in Peripheral Blood of Patients with Hepatocellular Carcinoma after Transcatheter Arterial Chemoembolization - 刘谨文 易继林 (Journal of Huazhong University of Science and Technology. Medical sciences, 2007)
In order to investigate the relationship between the VEGF level and the counts of dendritic cells （DCs） in peripheral blood of patients with hepatocellular carcinoma （HCC） before and after transcatheter arterial chemoembolization （TACE）, the peripheral blood was obtained from 37 patients with HCC who treated by TACE. The blood was obtained on the day before TACE, the first day, the 7th day and the 15th day after TACE respectively. The counts of DCs were quantified by flow cytometry. The plasma VEGF level was measured by ELESA kit. It was shown after TACE, the counts of DCs in peripheral blood were decreased significantly （P〈0.05）, and the VEGF level in peripheral blood was increased significantly （P〈0.05）. The counts of DCs in peripheral blood had an inverse correlation with the plasma VEGF level （r=-0.57, P〈0.05） after TACE. It was concluded that in patients with HCC after TACE, the increased plasma VEGF level appeared to have the effect to suppress the maturation of DCs, which may contribute to reduction of the body＇s anti-tumor immunity effect, with a consequence of recur and metastasis of tumor.